PENGARUH MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN GEOGRAFI TERHADAP LITERASI EKOLOGI SISWA SMA - Susanthi, Yuli; Khotimah, Nurul (Indonesian Journal of Environment and Disaster, 2025)
This research was aimed to analyze the effect of problem based learning model on ecological literacy of high school students. This study is a type of quasi-experimental research with a pretest-posttest control group design model. This study used two sample groups, namely the experimental group and the control group. The study was conducted at SMAN 1 Ngadirojo. The number of research subjects in each class was 35 students. The experimental group subjects were class XI IPS 1 and the control group subjects were class IPS 2. Data collection was carried out using test instruments and questionnaires through pre-test and post-test. Data analysis was carried out using independent t-test analysis techniques on the N-Gain Score value with a significance level of 0.05 through the SPSS 126 application. The results showed that the problem based learning model had a significant effect on students' ecological literacy with a significance value of 0.013 (significance value <0.05). These findings indicate that the problem-based learning model in geography learning has an effect on the ecological literacy skills of high school students.